Gender and Industrialization: Developments and Trends in the Context of Developing Countries - Alina Sorgner (Institute of Labor Economics (IZA), 2021)
This paper reviews the literature on the relationship between gender (in)equality and industrialization in the context of developing countries. It documents past developments, accounting for pre-industrial preconditions that might explain current differences in gender roles across societies. Moreover, it discusses the main drivers of the relationship between gender equality, economic development and structural change with a focus on the mechanisms driving this complex relationship. It provides novel empirical evidence of recent developments and the current state of gender equality in different spheres in developing countries at different stages of structural change. The study also identifies emerging trends, for instance, related to more recent technological advancements in Industry 4.0 and premature deindustrialization, and discusses their possible impacts on gender equality in developing countries. The ultimate aim of the paper is to identify knowledge gaps and to formulate relevant research questions that need to be addressed to design constructive policies aimed at promoting gender equality in developing countries.
Keywords: J16; O14; O33; 330; gender; industrialization; developing economies